How Australian swimmers peak - Pyne, D.; Goldsmith, W. (Australian Masters Swimming Coaching Newsletter, 1996)
This was a presentation to Athletics Australia 1996 Olympic Preparation Seminar. This article focuses on some physiological aspects of the periodisation and tapering of elite Australian swimmers preparing for the 1996 Atlanta Olympics. We aim to share some of the ways that swimmers are prepared for major competition. A fundamental principle of preparing athletes is that periodisation and tapering applies equally to all the different aspects of fitness such as endurance, speed, strength, flexibility and power. Tips: - The most important consideration is that peaking for performance is an active process. Put as much effort into the planning and execution of the tapering and peaking program as you do for regular training. - The annual plan and the competition calendar are essential tools. To achieve extraordinary results you need an extraordinarily good training program. Last year`s program may bring you last year`s results. - Make sure your athletes are able to train at close to race speed when required. This is achieved by the careful management of endurance, speed and recovery. - Plan broad details for a mesocycle, fine details for a microcycle, and adjust details on a daily basis. - Although the requirement for aerobic work applies to the middle distance and distance events, even the shorter sprint events may benefit from this type of training. - A more effective approach is to have a broad-based conditioning program. Too much concentration in one area eg weight training and neglect of others eg flexibility or cross training, may be a limiting factor. - Be proactive: make and dictate the move from volume to intensity, endurance to speed and training to racing. - When peaking, the development of race speed should take priority over conditioning work on the track, road or in the gym. - Control the intensity of training by speed (pacing), heart rate and perception of effort (by the athlete and coach) - don`t neglect any one factor. - The key of peaking is: reduce the volume and sharpen speed. Peaking is an active process of training and achieved by a well planned and executed training and recovery program.